2007
DOI: 10.1208/pt0802048
|View full text |Cite
|
Sign up to set email alerts
|

Stomach-specific drug delivery of 5-fluorouracil using floating alginate beads

Abstract: A multiple-unit-type oral floating dosage form (FDF) of 5-fluorouracil (5-FU) was developed to prolong gastric residence time, target stomach cancer, and increase drug bioavailability. The floating bead formulations were prepared by dispersing 5-FU together with calcium carbonate into a mixture of sodium alginate and hydroxypropyl methylcellulose solution and then dripping the dispersion into an acidified solution of calcium chloride. Calcium alginate beads were formed, as alginate undergoes ionotropic gelatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 24 publications
1
34
2
Order By: Relevance
“…Unlike previous reports (Shishu, Gupta, & Aggarwal, ), the addition of CaCO 3 significantly increased the EE, especially for the microspheres gelled in cross‐linking bath containing 2% acetic acid (Figure ), which could indicate that the calcium ions released from the carbonate contributed to the internal gelation of the alginate chains.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…Unlike previous reports (Shishu, Gupta, & Aggarwal, ), the addition of CaCO 3 significantly increased the EE, especially for the microspheres gelled in cross‐linking bath containing 2% acetic acid (Figure ), which could indicate that the calcium ions released from the carbonate contributed to the internal gelation of the alginate chains.…”
Section: Resultscontrasting
confidence: 77%
“…The EE results reported in this study are lower than previously described by Nayak, Jain, and Pandey () (77.61–82.48%), Shishu et al. () (71.85–86.45%), and Singh, Deol, and Kaur () (74.37–75.0%), however significantly higher than those reported by Ma et al. () (19.49–20.12%).…”
Section: Discussioncontrasting
confidence: 79%
“…Ionic gelation method, for preparation of floating beads (Whitehead et al, 1998;Talukder & Fassihi, 2004b, Pawar et al, 2008, was also adopted by a number of investigators. Different classes of pharmacotherapeutic agents were encapsulated in these systems, like anti-bacterial agent metronidazole (Murata et al, 2000;Sriamornsak et al, 2005;Ishak et al, 2007), anti-cancer agent like 5-fluorouracil (Shishu et al, 2007b), non-steroidal anti-inflammatory drug like piroxicam (Lee et al, 2001), anti-hypertensive agent like verapamil hydrochloride (Sawicki, 2002), and bronchodilator like theophylline (Yang et al, 2004). In a study (Gohel & Sarvaiya, 2007) it was revealed that gastroretentive tablets of rifampicin and isoniazid minimize the degradation of rifampicin and isoniazid in acidic medium because the developed system minimized the physical contact between the two drugs and also controlled release rifampicin in acidic medium.…”
Section: Low-density Systemsmentioning
confidence: 99%
“…The fully formed micro carriers were collected, washed with distilled water twice and subsequently air dried. 9,10,11 Floating alginate microspheres of cefixime with different types of co-polymers such as HPMC K4M, HPMCK 15M, and ethyl cellulose were prepared. The formulation details are given in Table 1, 2 & 3.…”
Section: Preparation Of Foating Alginate Microspheresmentioning
confidence: 99%